Secure transmission for cooperative NOMA systems with source‐relay selection - Shu Xu (Wiley, 2021)
Abstract Both cooperative non‐orthogonal multiple access (NOMA) and physical layer security (PLS) are promising techniques for future communication systems. This paper investigates the PLS performance of a cooperative NOMA system where multiple sources transmit a superposed message to two users by utilizing either amplify‐and‐forward (AF) or decode‐and‐forward (DF) relays in both non‐colluding and colluding eavesdropper scenarios. A source‐relay selection scheme is proposed for this system aiming at improving the secrecy performance. Additionally, the closed‐form expression of the secrecy outage probability (SOP) is derived for the proposed source‐relay selection schemes. It is demonstrated that in the proposed schemes, the theoretical results match well with the simulation results. In addition, the proposed schemes outperform the conventional OMA system in terms of SOP.